2014
DOI: 10.1007/s13277-014-2464-1
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Tim-3 as a therapeutic target in prostate cancer

Abstract: T cell immunoglobulin domain and mucin domain-containing molecule 3 (Tim-3) is a newly discovered immunomodulatory, which plays an important role in immunity regulation. Recent evidence suggests that Tim-3 is differentially regulated in a variety of tumors and has a potential as a therapeutic target. The aim of this study was to investigate the effect of Tim-3 on the development of prostate cancer (PCa). Tim-3 expressing on peripheral CD4+ T and CD8+ T cells was analyzed by flow cytometry. The relationships be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Recently, Ji et al (2015) and Komohara et al (2015) reported an increase in Tim-3 expression in non-small cell lung cancer infiltrated lymphocytes by immunohistochemistry and flow cytometry and in renal clear cell carcinoma tissue and CD204 + tumor-associated macrophages, respectively. Piao et al (2014) proved that Tim-3 expression was highly elevated in CD4 + and CD8 + T cells of prostate cancer patients, and not in patients with benign prostatic hyperplasia, by flow cytometry and immunohistochemistry, whereas Cao et al (2013) reported a significantly higher Tim-3-positive expression rate in cervical cancer tissues than that in cervical intraepithelial neoplasia and chronic cervicitis. Tumors with high Tim-3 expression have been reported to present a higher metastatic potential and lower overall survival, suggesting a close association between Tim-3 expression and tumor occurrence and metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Ji et al (2015) and Komohara et al (2015) reported an increase in Tim-3 expression in non-small cell lung cancer infiltrated lymphocytes by immunohistochemistry and flow cytometry and in renal clear cell carcinoma tissue and CD204 + tumor-associated macrophages, respectively. Piao et al (2014) proved that Tim-3 expression was highly elevated in CD4 + and CD8 + T cells of prostate cancer patients, and not in patients with benign prostatic hyperplasia, by flow cytometry and immunohistochemistry, whereas Cao et al (2013) reported a significantly higher Tim-3-positive expression rate in cervical cancer tissues than that in cervical intraepithelial neoplasia and chronic cervicitis. Tumors with high Tim-3 expression have been reported to present a higher metastatic potential and lower overall survival, suggesting a close association between Tim-3 expression and tumor occurrence and metastasis.…”
Section: Discussionmentioning
confidence: 97%
“…The expression of Tim-3 in peripheral blood monocytes and in tumor tissues has been suggested to be prognostic in prostate cancer (18). Tim-3 may affect development and progression, and be a therapeutic target in prostate cancer (19). The role of Tim-3 in human tumorigenesis is not limited to prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Since this discovery, countless studies have found that exhaustion occurs in almost any setting where persistent antigen exposure occurs, and that PD1 blockade can partially restore the function of exhausted CD8 Tcells. Exhausted T-cells are found in most cancers, including breast, prostate, colon, and melanoma [53][54][55][56][57]. A key feature of exhaustion is the inability of T-cells to proliferate in response to antigen, and therefore the fact that PD1 is so successful in melanoma makes it unlikely that vaccination could ever be successful alone; the Tcells are functionally exhausted and non-responsive to vaccine antigen.…”
Section: Cd8 T-cell Exhaustion and Vaccinesmentioning
confidence: 99%
“…TIM3 is another molecule that contributes to CD8 T-cells exhaustion discovered in HIV patients, and blockade of TIM3 was found to restore the functionality of exhausted CD8 T-cells isolated from HCV patients [63,64]. Several observations have now been made in human patients with cancer and mouse models of cancer that show that tumor antigen specific CD8 T-cells express high levels of TIM3 [39,54,55,65]. No clinical trials of TIM3 blockade have been reported yet, but in vitro experiments have found that blockade of PD1 and TIM3 improved the response of CD8 T-cells from patients with melanoma against the NY-ESO-1 antigen, further suggesting that rescuing exhausted CD8 cells before immunization could generate a better immune response to the vaccine [66].…”
Section: Cd8 T-cell Exhaustion and Vaccinesmentioning
confidence: 99%